Analisa Minat Penggunaan Aplikasi TB eScoring dengan Pendekatan Technology Acceptance Model (TAM) - Udayanti, Erika Devi; Nugroho, Fajar Agung (Edu Komputika Journal, 2018)
TB eScoring is an application for medical aids in diagnosis of child tuberculosis to perform patient symptom scoring parameters. Application aimed to minimize underdiagnose and overdiagnose cases in pediatric patients suspected tuberculosis. To achieve successful implementation of tuberculosis diagnosis of children with TB eScoring application require users understanding about adoption rate of TB eScoring application. This research aims to analyze interest in the use of information technology in this case TB eScoring application. The approach of technology acceptance model (TAM) by modifying the adopted constructs is Perceive usefulness, perceive ease of use and intention to use. Linear regression modeling is used to test the existing hypothesis. The results obtained are all hypotheses accepted based on tests conducted to the relationship of each variable. From the results of the research obtained that usability variables significantly have a positive relationship to the interest in use. In addition, the ease variable also has a positive relationship to the interest in the use of TB eScoring application. Both significance value of is 0.002, smaller than 0.05.